Murottal Qur’an to Lower Anxiety Rate on Pre-Operative Patients - Iis Ismayanti; Ade Fitriani; Gita Puspa Jayantika; Shofi Nurwahidah; Fidya Anisa Firdaus; Henri Setiawan (International Journal of Nursing and Health Services (IJNHS), 2021)
The preoperative phase was an action before surgery which was the basis for success in the next stage. In this phase, psychological disorders could occur, for example, anxiety. The feeling of anxiety that was felt by this preoperative patient might be overcome immediately, because it would hinder the future process, namely when the surgery was carried out, this was because feelings of anxiety could cause physiological changes. The purpose of this literature review was to describe the change in anxiety levels in preoperative patients after being given murottal Al-Qur'an therapy. This research design was a descriptive analysis with a literature review approach. Search for articles using 8 journal databases, namely PubMed, ScienceDirect, TaylorFrancis Online, JSTOR, SAGE Journal, Willey Online Library, Springer, and Google Scholar. Selection was carried out by assessing articles that meet the inclusion criteria with a publication range of 2015-2021, in English and Indonesian, and open access to full text pdf, while the exclusion criteria were book chapters, abstract proceedings, and posters. A total of 12 articles that met the inclusion criteria were reviewed. All articles were fully reviewed, specifically criticized and rated using the Critical Appraisal Skills Programmed instrument with 321 respondents. The results of the review showed that murottal Al-Qur'an therapy had a positive effect in lowering anxiety levels in the nursing process in preoperative patients.